Experiencing the Gothic Style. Issue 1 (16th December 2019) - de Jong, Sigrid
Abstract : Eighteenth-century French accounts of Gothic churches are testimonies of both negative preconceptions about the Gothic style formed through reading and actual positive experiences of Gothic buildings. While Goethe at Strasbourg Cathedral reconciled the discrepancy between preconceived opinion and opinion based on experience by referring to history, many 18th-century French architects avoided any historicist interpretation after they visited churches. They continued to express a dislike for Gothic ornament, but also found they could admire the spaciousness of Gothic churches. Jacques-Germain Soufflot, who analysed the church of Notre Dame in Paris by moving through it, suggested disregarding 'entirely the chimerical and bizarre ornaments of the Goths', in favour of experiencing the church's spatial qualities. This article argues that we can only understand how ideas about the Gothic style changed if we study them from the point of view of the observer of these buildings. This turnaround happened precisely through experience, which allowed 18th-century architects to reconcile their conflicting feelings. By moving through the buildings, they came to understand the idiosyncrasies of the Gothic, from its ornamentation to its spatiality. Beginning with Soufflot's lecture of 1741, 'Mémoire sur l'architecture gothique', this article analyses similar experiences of 18th-century architects and writers who focussed not on historicization (like Goethe did) but on the ahistorical aspects of the Gothic. It thus aims to unveil the complexity of the workings of style.